AB0507 Role of IL-10 Gene Polymorphism in Clinicopathological Presentations and Treatment Response in Lupus Nephritis Patients. (10th June 2014) - Elzawawy, A.; Tayel, M.; Sayed, M.; Waked, E.; Elgendy, S.; Abdelrazek, S.
Abstract : Background: Lupus nephritis can affect up to 70% of the SLE population elevated serum IL-10 levels were observed in SLE patients and have been shown to be associated with disease activity. It enhances B-cell surivival, proliferation, differentiation, Genotypic variations in the human IL-10 promoter may account for individual variation in IL-10 production and in turn, susceptibility to a particular disease. Objectives: to investigate the -592 A/C polymorphism in patients with lupus nephritis with different pathological classes and to assess its influence on IL-10 secretion in vivo. Methods: Patients were divided into: – Group I: lupus nephritis group (40 patients). – Group 2: SLE non nephritis group (20 patients). All patients in this study were subjected to the following: Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) Immunological profiles: ANA (Antinuclear Antibody) Anti double stranded DNA titer (Anti-ds DNA) Determination of –592 A/C polymorphisms in the IL-10 gene promoter Detection of serum of IL-10 level. All SLE patients with clinical and laboratory evidence of renal involvement will be subjected to renal core biopsy. Results: There is no statistically significant differences in the distribution of the 592 genotypes, or the alleles frequencies between (group 1) and (group 2). There is no statistically significant difference between AC/CC and AA genotypes with different clinical and laboratory parameters in (group 1).Renal biopsy is done for all 40 patients of (group 1). According to the ISN/RPS 2003 classification (96), 12 patients (30%) are classified as class III LN, 16 patients (40%) are classified as class IV LN, 7 patients (17.50) are classified as class V, 4 patients (10%) are classified as class IV+V and 1 patient (2.50%) is classified as class VI. Class I and class II are not detected in the study.According to activity and chronicity indices, (96) class IIIa, IVa and IVa+V are classified as active classes while class IIIc and IVc are classified as chronic classes. There was no statistical significant difference in the distribution of AC and CC genotypes among different LN classes. Decrease in serum level of serum IL-10 in both active and chronic classes of LN does not reach the statistical significance. Conclusions: IL-10 gene –592 A/C polymorphism, was not associated with susceptibility to LN or the difference of the patients' serum IL-10 levels, References: Lowe PR, Galley HF, Abdel-Fattah A, Webster NR. Influence of interleukin-10 polymorphisms on interleukin-10 expression and survival in critically ill patients. Crit Care Med 2003; 31: 34-8. Lowe PR, Galley HF, Abdel-Fattah A, Webster NR. Influence of interleukin-10 polymorphisms on interleukin-10 expression and survival in critically ill patients. Crit Care Med 2003; 31: 34-8. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3084